2018
DOI: 10.1371/journal.pone.0190301
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin is lower in African American men with diabetes and associates with psycho-social and metabolic health factors

Abstract: ObjectiveRecently, it has been suggested that oxytocin (OT) has a role in metabolism and neuropsychiatry health and disease, and therefore, it may represent a potential therapeutic target. The current study aimed to investigate relationships between OT and glycemic status along with psycho-social and behavioral factors. Design and methodsA total of 92 obese or overweight, African American, male subjects were enrolled in the study. Biometric and biochemical data were collected including oral glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…In other murine studies, subjects administered OT exhibited increased levels of the hormone (i.e., OT) in serum and in plasma thus supporting our observation through the assigned Raman peak. Elsewhere, it was reported that OT levels in blood of obese human subjects having type II diabetes mellitus were significantly lower compared with healthy ones . The band around 478 cm −1 is associated with both fructose and glucose's skeletal vibrations with tentative assignments C─C─C, C─C─O, C─O deformations, and C─C torsional vibrations .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In other murine studies, subjects administered OT exhibited increased levels of the hormone (i.e., OT) in serum and in plasma thus supporting our observation through the assigned Raman peak. Elsewhere, it was reported that OT levels in blood of obese human subjects having type II diabetes mellitus were significantly lower compared with healthy ones . The band around 478 cm −1 is associated with both fructose and glucose's skeletal vibrations with tentative assignments C─C─C, C─C─O, C─O deformations, and C─C torsional vibrations .…”
Section: Resultsmentioning
confidence: 98%
“…[17] In a study on African American males, the levels of OT in blood of type II diabetic males were found to be lower than in healthy ones. [18] In the same study, persons with higher levels of OT had lower body weights. All these findings indicate a special role OT plays in the treatment and prevention of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In humans, studies have shown that peripheral OT levels are elevated in obesity and the metabolic syndrome, and correlate with BMI and fat mass . Conversely, OT concentrations may be lowered in the presence of overt diabetes . Acutely, intranasal OT administration reduces caloric intake with a preferential reduction in fat consumption; as in animals, these effects are more pronounced in obesity .…”
Section: Physiological Effectsmentioning
confidence: 99%
“…21,22 Conversely, OT concentrations may be lowered in the presence of overt diabetes. [23][24][25] Acutely, intranasal OT administration reduces caloric intake 26,27 with a preferential reduction in fat consumption 26 ; as in animals, these effects are more pronounced in obesity. 27 These actions may be mediated at least in part by modification of hedonic as well as homoeostatic pathways.…”
Section: Phys I Olog I C Al Effec Tsmentioning
confidence: 99%